The Relationship of Histopathological Features of the Fallopic Tubes with the Expression of P53 Mrna and YY1 Mrna in Mucinous Ovarian Carcinoma - Noor, Istikomah; Nawangtantrini, Gita; Aditiyono (International Journal of Medical Science and Clinical Research Studies, 2024)
Introduction: Ovarian cancer is the third most common cancer in Indonesia after breast cancer and cervical cancer. The global prevalence of mucinous ovarian carcinoma is lower than other subtypes, but the relative frequency of the mucinous subtype in Indonesia is the third highest after Singapore and South Korea. Ovarian cancer develops in the tubal fimbria before metastasizing to the ovaries. Genes involved in the carcinogenesis of mucinous ovarian carcinoma include KRAS, BRAF, p53. The expression of YY1 (Yin Yang 1) is associated with increased survival in ovarian cancer patients. Objective: The aim of this study was to determine the relationship between histopathological features of the fallopian tubes and the expression of p53 mRNA and YY1 mRNA. Methods: This study used a cross sectional research design. The sampling technique used was purposive sampling. The sample for this study were 27 mucinous ovarian carcinoma patients at Regional General Hospital Prof. Dr. Margono Soekarjo Purwokerto. Examination of p53 and YY1 expression using qPCR and tubal histopathology using hematoxylin eosin staining. Results: . Of the 27 study samples, 24 patients had high p53 mRNA expression and 3 patients had low p53 mRNA expression. Meanwhile, 24 patients had low expression of YY1 mRNA expression, 3 patients had high expression. Based on the results of the Fisher’s Exact statistical test analysis, there was no relationship between tubal histopathological features and p53 mRNA expression in mucinous ovarian carcinoma patients, with a significance value (p) of 0.231. There was no relationship between tubal histopathological features and YY1 mRNA expression with a significance value (p) of 0.569. Conclusion: There is no relationship between the histopathological features of the fallopian tubes and the expression of p53 mRNA and YY1 mRNA